Upaya Penanggulangan Covid-19 dalam Keluarga Civitas Akademika Universitas Nurul Jadid - Vivin Nur Hafifah; Septi Nur Badriah; Putri Nur Malasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Covid-19 is a disease that attacks the respiratory system, the symptoms are runny nose, sore throat, cough and fever. This study aims to determine the efforts to overcome Covid-19 in the family of the academic community at Nurul Jadid University, Probolinggo. This type of research was qualitative with a phenomenological approach. Data collection was carried out on February 2, 2021 after obtaining research permission. The participants involved were 8 people who were selected by purposive sampling technique, including 3 lecturers from the Faculty of Health, 2 lecturers from the Faculty of Engineering, 2 lecturers from the Faculty of Islamic Religion and 2 educational staff from the Faculty of Health). Data were collected through structured interviews. Interviews were carried out by implementing health protocols such as wearing masks, physical distancing, and washing hands before and after the interview. Data analysis was done manually using thematic analysis method. The results showed that the family of the Nurul Jadid University academic community had made efforts to overcome Covid-19, including: wearing masks when working, keeping a distance, washing hands, increasing immunity, applying correct cough etiquette, changing clothes or bathing when you get home, controlling disease. accompanying and routinely cleaning objects that are often handled with disinfectant.Keywords: Covid-19; countermeasures; family ABSTRAK Covid-19 adalah penyakit yang menyerang sistem pernafasan, gejalanya berupa pilek, sakit tenggorokan, batuk dan demam. Penelitian ini bertujuan untuk mengetahui upaya penanggulangan Covid-19 dalam keluarga sivitas akademika Universitas Nurul Jadid, Probolinggo. Jenis penelitian ini adalah kualitatif dengan pendekatan fenomenologi. Pengambilan data dilakukan pada tanggal 02 Februari 2021 setelah mendapatkan izin penelitian. Partisipan yang terlibat yaitu 8 orang yang dipilih dengan teknik purposive sampling, meliputi 3 dosen Fakultas Kesehatan, 2 dosen Fakultas Teknik, 2 dosen Fakultas Agama Islam dan 2 staf kependidikan Fakultas Kesehatan). Data dikumpulkan melalui wawancara terstruktur. Wawancara dilaksanakan dengan menerapkan protokol kesehatan seperti pemakaian masker, physical distancing, dan mencuci tangan sebelum dan setelah wawancara. Analisis data dilakukan secara manual menggunakan metode analisis tematik. Hasil penelitian menunjukkan bahwa keluarga civitas akademika Universitas Nurul Jadid telah melakukan upaya penanggulangan Covid-19 antara lain: memakai masker saat bekerja, menjaga jarak, mencuci tangan, meningkatkan imunitas, menerapkan etika batuk yang benar, mengganti baju atau mandi sesampai di rumah, mengendalikan penyakit penyerta serta membersihkan secara rutin benda-benda yang sering dipegang dengan desinfektan.Kata kunci: Covid-19; penanggulangan; keluarga